If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3/3(g-5)=6
We move all terms to the left:
3/3(g-5)-(6)=0
Domain of the equation: 3(g-5)!=0We multiply all the terms by the denominator
g∈R
-6*3(g-5)+3=0
Wy multiply elements
-18g(g+3=0
| 9-4n=-5n | | 3x-5=2x+180 | | 5x-1=7x+9-4x | | 27y=24y | | 1/3(g-4)=6 | | -3(x-6)=5x+34 | | (8x-3)+(4x+9)=180 | | 48=x*4^2 | | 175m-75m+57,600=60,600-200m | | -2.4+1.1t=1.9t | | 8.2q-13.37=-7.2q+7.67+9.76 | | 4x+9(-8)=-14 | | -11d-(-9d)+12d=-10 | | 71+3x=89 | | –6(h−79)=–54 | | 0.5n+1.7-0.2n=3.2-0.3n | | 4x-11=4x+15 | | p=1/34.6 | | 4x+9(-9)=-14 | | 2=-2*4+a | | 24=x*2^2 | | -3(d+8)=24 | | p=1/34.666666666667 | | 180=(7x+6)+5x+42 | | x=60/6 | | -4k+9=42 | | -9v+7=-7(v+7) | | x+x-13=25 | | x=(-4+1)^2-11 | | 10d-10d+5d=5 | | -15y+17=-15+18-17y | | 4x+3+31x-5=173 |